Exploring Sustainable Economic Growth: Promoting Green Development Productivity through Decentralized Environmental Policy and Regional Competitiveness - Moh Najikhul Fajri; Siti Munawaroh (The Journal of Indonesia Sustainable Development Planning, 2023)
The freedom of regions in regulating territories is now being promoted with the decentralization of environmental policies. This policy serves as the forerunner in empowering regions to function autonomously, thereby playing a role in practical politics. Therefore, this research aimed to analyze the role of decentralization of environmental policy and local government competition in navigating green development productivity in Indonesia. The slack base model and dynamic panel regression were used to generalize the method of the moment. The results showed that the decentralization of environmental policies and local government competition negatively affected the productivity of green development. Meanwhile, budget allocations for research and development, along with strategic initiatives in economic sectors such as agriculture and mining, showed a substantial positive effect.